Comparison Adoption Application Music Playlist Joox, Spotify, & YouTube Music Using Diffusion Technology Theory - Setiyani, Lila; Fathurrozaq, Shiddieq; Awalludin, Dudi (PT. Riset Press International, 2023)
Application playlist music start lots favored by people in Indonesia. There are several playlist music presented in the Play Store and the App Store. Among them Joox, Spotify, YouTube Music, and more lots again. This is interesting for we find out which one is the most suitable and popular in society. Objective study is to know comparison of Playlist Music applications among them Joox, Spotify, and YouTube Music among society. Diffusion Technology Theory was chosen as the framework for evaluating the reception of 3 apps. The procedure study started with collecting data based on variables from Diffusion Technology Theory. Collected data processed with the use of Application smart pls. Research results This shows variable influencing variables _ reception Joox Music Playlist application, Spotify and YouTube Music, among others Profit Relative (RA) effect to Activity Listen Music (Y), Compatibility (CT) matters to Activity Listen Music (Y), Complexity (CX) matters to Activity Listen Music (Y), Triability (TR) effect to Activity Listen to Music (Y), Observability (OB) influence to Activity Listen to Music (Y). Research results this can be used by providers of Playlist Music apps to develop possible features, liked by fans Music Playlists application.